Participation of S and Se in hydrogen and chalcogen bonds - Scheiner, Steve (CrystEngComm, 2021)
This article reviews the history and the current state of knowledge concerning the ability of the heavy chalcogen atoms S and Se, and to some extent Te, to participate in a H-bond as either proton donor or acceptor. These atoms are nearly as effective proton acceptors as O, and only slightly weaker as donor. They can also participate in chalcogen bonds where they act as electron acceptors from a nucleophile. These bonds rapidly strengthen as the chalcogen atom becomes larger: S < Se < Te, or if they are surrounded by electron-withdrawing substituents, and can exceed that of many types of H-bonds. Experimental and computational evidence indicates that both H-bonds and chalcogen bonds involving S and Se occur widely in chemical and biological systems, and play an active role in structure and function. The heavier chalcogen atoms S, Se, and Te can each participate in a range of different noncovalent interactions. They can serve as both proton donor and acceptor in H-bonds. Each atom can also act as electron acceptor in a chalcogen bond.